Herpetofauna dari Hutan Desa Ubadari, Fakfak: Keanekaragaman, Kepadatan, dan Upaya Konservasi - Keliopas Krey; Petrus Tawurutubun (Igya ser hanjop: Jurnal Pembangunan Berkelanjutan, 2021)
Obadari forest is one of the important herpetofauna habitat. The forest lies on diverse geomorphology and topography including creeks, vertical caves with small springs. These formations have influenced the diversity of herpetofauna in the forest. This study was designed to document herpetofauna species in Obadari Forest, Obadari, Fakfak. We used VAES at a 2000-meter transect randomly located within the forest. Patch survey was also used to sample habitats that not within the transect. Reptiles and amphibians were observed during days and nights. Direct interview with member of Obadari community to gather information on what are the common herpetofauna species and how would they react in such encounter. About 45 species herpetofauna were recorded during this study between 2-15 February 2021, of which 15 species frogs from Hylidae, Microhylidae and Ranidae: and 30 species of reptiles from Scincidae, Geckonidae, Varanidae, Colubridae, Pythonidae and Elapidae. Although these data relative sufficient to represent all herpetofauna in this forest, we believe more may yield more species. This result also indicate that Obadari forest is an important habitat for Papuan herpetofauna species